2015
DOI: 10.1016/j.ijheatmasstransfer.2014.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional liquid and vapour distribution in the wick of capillary evaporators

Abstract: a b s t r a c tHeat and mass transfer with liquid-vapour phase change in a representative unit cell of a capillary evaporator is studied using a mixed pore network model. The model combines the computation of temperature and pressure fields in vapour and liquid pores according to mean field approaches with pore scale invasion rules depending on the capillary pressure thresholds associated with each local constriction between two pores. The metallic body through which heat is transferred to the porous wick is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…By consequence, in accordance with the work of Mottet et al [13], the vapor pocket assumption is valid for higher heat fluxes. Recently, Boubaker and Platel [14] presented a transient model of the whole CPL where it supposes the existence of vapor pocket inside the porous wick.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…By consequence, in accordance with the work of Mottet et al [13], the vapor pocket assumption is valid for higher heat fluxes. Recently, Boubaker and Platel [14] presented a transient model of the whole CPL where it supposes the existence of vapor pocket inside the porous wick.…”
Section: Introductionsupporting
confidence: 83%
“…The visualization experiments on a two-dimensional porous wick confirmed the existence of a stable vapor pocket underneath the heated surface. Later on, Mottet et al [13] continued working on the same topic by developing a steady 3D model to describe the heat and mass transfers inside the porous wick. It was demonstrated that, for a moderate heat flux between 3.7 W/cm 2 and 7.8 W/cm 2 , the phase distribution within the wick is characterized by the coexistence of both the liquid and vapor phases underneath the casing.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13]). However, a recent work [7] highlighted that a two-phase zone actually exists under the casing, as already supposed in [14][15][16][17], calling into question the relevance of the ''vapour pocket" assumption in a three-dimensional capillary evaporator unit cell. As pointed out in [13], the most interesting regime, corresponding to the best evaporator performances, is actually the regime in which there is no vapour pocket and where liquid and vapour coexist within the wick.…”
Section: Introductionmentioning
confidence: 97%
“…Very recently, Mottet et al (2015) and Nishikawara et al (2015) presented 3D pore network models for different fluid configurations. In Mottet et al (2015), the thermally conductive fin is made of a solid metallic blade whereas in Nishikawara et al (2015) an etched porous fin is considered.…”
Section: Introductionmentioning
confidence: 99%
“…In Mottet et al (2015), the thermally conductive fin is made of a solid metallic blade whereas in Nishikawara et al (2015) an etched porous fin is considered. The 3D simulation results indicate that between the saturated wick and the dry-out regime there is another operating regime, the so-called two-phase zone regime, in which the liquid and the vapor phase coexist below the fin.…”
Section: Introductionmentioning
confidence: 99%